Non-cirrhotic Hyperammonemia: A Risk Factor for Altered Mental Status - Yadav, Umesh; Kumar Sah, Prashant; L, Mahadevamma (Journal of Pharmacy Practice and Community Medicine)
Hyperammonemia refers to a rise in the level of ammonia in the blood. Ammonia is a normal component of all body fluids and the body excretes excess ammonia as urea after synthesis in the liver by enzymes commonly called urea cycle enzymes. If ammonia builds up in the blood, it can cross the blood brain barrier and cause neurological disorders associated with hyperammonemia. Altered mental state is a medical term that describes any change in mental functioning that involves consciousness or cognition or both. Elderly patients are more likely to experience an altered mental state, mainly because they have multiple vulnerability factors, such as old age, dementia, comorbidity and functional dependence. A 64 years Indian male patient was admitted to hospital with the complaints of deterioration in mental status, aggressive behavior for about 1 week. His home medications include olanzapine 10 mg po BD, senna lax 8.6 mg 2 tablets before bed, docusate sodium 100 mg po 2 tablets before bed and sucralfate. The serum ammonia was 92 mmol/l on first day. Liver function tests were normal. He was treated with lactulose enema and halodol. The high level of ammonia in the blood and the rapid resolution of symptoms along with the reduction of its ammonia level in the blood lead us to suspect that hyperammonemia may have explained its presentation.
Keywords: Hyperammonia; Neurological disorders; Altered mental state; Non-cirrhotic; Halodol; Lactulose.